Tipy informacij dlja poverchnostno-semantičeskogo komponenta modeli smysl-tekst - Apresjan, Jurij D. (Wiener Slawistischer Almanach - Sonderbaende, 1980)
This book presents a new view point on some problems of semantics within the framework of the "Meaning - Text" model introduced to linguistics by I. A. Mel'čuk, A. K. Žolkovskij and Ju. D. Apresjan. In addition to some new formalisms and concepts it provides a great number of specific informal semantic analyses and thus gives a good idea of Apresjan's approach to semantics. Zsfassung in engl. Sprache: Types of information for the surface- semantic component of the 'meaning - text' model. Zsfassung in engl. Sprache: Types of information for the surface- semantic component of the 'meaning - text' model.